IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN SISWA BARU MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (Study Kasus : SMK Negeri 3 Kuningan) - Yayan Sopyan; Sugeng Supriyadi; Erik Kurniadi (FKOM UNIKU, 2016)
Acceptance of New Students is one of the existing processes in educational institutions such as schools that are useful for screening prospective students who are selected according to the criteria determined by the school to be students students. In general, the process of Admission New Students through the stages of registration, selection tests and announcement of student acceptance.In this research, its application to SMK Negeri 3 Kuningan where in the process of New Student Admission must be decided quickly and precisely therefore it is needed Decision Support System to assist the committee of PPDB in decision making. The method used in this Decision Support System is by Simple Additive Weighting (SAW) method.In building this system using the software development method Waterfall model and required tools used for the design include: Flowmap, Context Diagram, Data Flow Diagram, Entity Relationship Diagram And Data Dictionary, created using Microsoft Visio applications. Data collection methods used in the preparation of this thesis is Observation, Library Studies and Interview. This system was developed using PHP and MySQL as database server.The result of this research is decision support system in new student acceptance by using Simple Additive Weighting (SAW) method which gives more optimal result in management and value calculation so that PPDB committee can give quick decision.Keywords: New Student Acceptance, Simple Additive Weighting (SAW), Waterfall, DFD, PHP MySQL